Sosialisasi Komunikasi Kebencanaan dalam Meningkatkan Kesadaran Mitigasi Bencana Alam pada Siswa Sekolah Dasar 09 Cibadak Sukabumi - Muhamad, Pagi; Sentosa, Angela Jani; Panggabean, Sahara Uli; Ramadhan, Alfajri; Dharmawicaesa, Narindra; Otami, ⁠Dika (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
This community service aims to raise disaster mitigation awareness among students at SDN 09 Cibadak, Sukabumi, an area prone to natural disasters such as earthquakes and landslides. Using a participatory approach, the program was conducted through interactive lectures and disaster simulations. Evaluation was carried out using pre-tests and post-tests to measure the improvement in students' knowledge. The results showed a significant increase in students' understanding of disaster mitigation steps. The disaster simulation effectively trained students to respond to emergency situations. This activity is crucial for building student preparedness and fostering a disaster-aware culture at school and in the surrounding community, potentially minimizing the risk of casualties in future disasters.